ANALISIS STRATEGY DIAMOND PADA UMKM WARUNG CINTA DI SEKITAR UIN RADEN INTAN - Feliza Sara Ridwan; Sonia Wulandari; Vicky F Sanjaya (Jurnal Akuntansi Dan Manajemen, 2025)
This study analyzes the business strategy of Warung Cinta, a micro–culinary enterprise located near UIN Raden Intan Lampung, using the Strategy Diamond framework by Hambrick & Fredrickson (2001). The research aims to understand how a student-oriented food business develops practical strategic decisions. A qualitative case study approach was applied, with data gathered through semi-structured interviews with the owner, complemented by observation and documentation. Thematic analysis was used to interpret the data. Findings show four key elements: an arena targeting the student market; vehicles based on fully independent operations; differentiation through a single-price system of Rp10,000, buffet-style service, and homemade flavors; and an economic logic grounded in cost efficiency and cross-subsidization to maintain price stability. These insights demonstrate how the Strategy Diamond can be implemented in micro-enterprises without formal strategic planning and offer practical guidance for campus culinary MSMEs in formulating simple yet consistent strategies. Future studies are recommended to examine digitalization as an opportunity for expanding student-focused food services.